86.2k views
3 votes
–3x + 1 + 10x = x + 4

2 Answers

0 votes
Alright so I will solve and explain as I go :)

First, let's combine like terms.

-3x + 1 + 10x = x + 4
7x + 1 = x + 4

Now, subtract the one from the left. (we do this to combine terms)

7x + 1 = x+ 4
7x = x + 3

Now subtract the x from the right. (this is also to combine terms)

7x = x + 3
6x = 3

Finally, divide by 6 on both sides.

6x = 3
x = 1/2 or 0.5

Hope this helps!


User Mitemmetim
by
5.1k points
4 votes
-3x+1+10x=x+4
1+7x=x+4
6x=3
x=.5
User Iva Kam
by
5.1k points